Modelling of immunosensor response: the evaluation of binding kinetics between an immobilized receptor and structurally-different genetically engineered ligands - Balevicius, Zigmas; Talbot, Julian; Tamosaitis, Linas; Plikusiene, Ieva; Stirke, Arunas; Mickiene, Gitana; Balevicius, Saulius; Paulauskas, Andrius; Ramanavicius, Arunas (Sensors and actuators. B, Chemical, 2019)
[Display omitted] •Binding kinetics between immobilized receptor and several genetically engineered ligands (GELs) was evaluated.•GELs were differing by molecular mass and/or by the number of binding sites available for the binding of receptor.•GCSF-Receptor, which binds glycoprotein granulocyte colony stimulating factor (GCSF), was immobilized.•Mathematical modelling was applied for the description of interaction between GCSF-Receptor with GCSF-based ligands.•Binding of GCSF-Receptor with GCSF-homodimer ((GCSF)2) was characterized by multi-stage kinetics. In this research we have evaluated the binding kinetics between an immobilized receptor and several genetically engineered ligands, differing by molecular mass or by the number of binding sites available for the binding to the receptor. Genetically engineered protein (GCSF-Receptor), which contains some antibody parts (Fc domain) and at some extent is similar to antibody because also has two binding sites that selectively bind another protein – glycoprotein granulocyte colony stimulating factor (GCSF), which was immobilized on a thin gold layer in order to design an immunosensor sensitive to GCSF. Three structurally different GCSF-based proteins were genetically-engineered and evaluated as ligands, which selectively bind to immobilized GCSF-Receptor: (i) GCSF monomer (mGCSF), (ii) GCSF-homodimer consisting of two via polypeptide Lα-based linker ‘fused’ GCSF molecules ((GCSF)2Lα) and (iii) GCSF-heterodimer (SCF-Lα-GCSF), which is based on a native GCSF molecule ‘fused’ via Lα-based linker with another protein – a soluble part of stem cell factor (SCF). SCF, unlike GCSF, does not contain any site suitable for GCSF-Receptor binding. The ligands differ by: (i) molecular mass – (GCSF)2Lα and SCF-Lα-GCSF F are two times heavier than mGCS, (ii) number of binding sites – mGCSF and SCF-Lα-GCSF have one binding site, while (GCSF)2Lα has two. The binding kinetics of mGCSF, (GCSF)2Lα, and SCF-Lα-GCSF with immobilized GCSF-Receptor was investigated using total internal reflection ellipsometry. The interaction kinetics of the mGCSF and SCF-Lα-GCSF are both well described using a standard Langmuir kinetics model. However, receptor-ligand association and dissociation rates in the case of SCF-Lα-GCSF ligand are about 10 times lower than that of mGCSF. The association rate of (GCSF)2Lα is about half of that of the mGCSF, which can be explained by the smaller diffusion coefficient of the larger molecule. Moreover, unlike SCF-Lα-GCSF, the (GCSF)2Lα adsorption kinetics cannot be adequately described by the standard Langmuir kinetics model and surface regeneration (induced by ‘washing’) experiments illustrate that (GCSF)2Lα, unlike the mGCSF and SCF-Lα-GCSF, is irreversibly bound to the surface modified by immobilized GCSF-Receptors. Therefore, to describe binding kinetics in the case of (GCSF)2Lα we have applied advanced kinetic model based on three protein association stages (three-stage kinetics model) in which (GCSF)2Lα forms several different intermediate complexes with GCSF-Receptor. This model precisely describes the time-varying surface concentration of (GCSF)2Lα bound to surface modified by immobilized GCSF-Receptors. In addition to the bioanalytical-aspects possible improvement of GCSF-based drugs is discussed.